2021
DOI: 10.1016/j.ijid.2020.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral alterations in West African HIV and non-HIV adults aged ≥50: An MRI study

Abstract: To cross-sectionally describe brain alterations in PLHIV aged above 50 years old, receiving antiretroviral treatment (ART) and living in Senegal compared to HIV-negative subjects. Methods: Twenty PLHIV and 26 HIV-negative subjects with comparable socio-demographic and clinical characteristics underwent an MRI exam (3D-T1 and FLAIR sequences). Global atrophy and White Matter Hyperintensities (WMH) were evaluated. After assessing the feasibility and acceptability of MRI scans in this population, we described atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…40,41 More specific to HIV, a previous study with PLWH on ART found that women were less likely to present with global atrophy. 38 We have previously reported that HIV seropositivity is associated with brain WMHs, analyzed qualitatively through manual scoring by expert neurologists from this cohort, and may be mediated by cardiovascular comorbidities. 11 Out of the 376 total scans herein, there were 155 overlapping MRI scans, and the results showed a strong correlation between C-DEF's quantitative measurement of WMH volume and Fazekas score.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…40,41 More specific to HIV, a previous study with PLWH on ART found that women were less likely to present with global atrophy. 38 We have previously reported that HIV seropositivity is associated with brain WMHs, analyzed qualitatively through manual scoring by expert neurologists from this cohort, and may be mediated by cardiovascular comorbidities. 11 Out of the 376 total scans herein, there were 155 overlapping MRI scans, and the results showed a strong correlation between C-DEF's quantitative measurement of WMH volume and Fazekas score.…”
Section: Discussionmentioning
confidence: 92%
“…Most studies have found no significant difference or no rapid worsening of WMH in PLWH after 2 years of follow-up, possibly highlighting the heterogeneity and comorbidities affecting WMH in any cohort of PLWH. 9,13,14,28,38 Indeed, the difference in WMH for black and white participants approached significance, with black participants having a 50% faster increase in WMHs over time. These race disparities should be explored more in the future, especially given that HIV and cardiovascular risk factors affect the black community disproportionately.…”
Section: Discussionmentioning
confidence: 93%
“…In SSA, to our knowledge, few data are available on the relationship between cardiovascular risk and cognition. One recent study in Senegal reported an association between hypertension and brain atrophy among PLHIV aged 50 years old or above [ 68 ] but due to limited sample size, the authors could not go further in the analyses and no cognitive evaluation was included. As cardiovascular diseases/risks factors and aging are associated with neuronal injury and inflammation in PLHIV stable on ART, some researchers suggest a tripartite model of HIV infection, aging, and cardiovascular disease/risk factors to explain neurocognitive impairment in PLHIV [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Beyond NCDs, MRI can play a paramount role in the management of infectious diseases, such as HIV and malaria. [21][22][23] Furthermore, in the context of a growing global cancer burden, access to imaging services can avert millions of cancer deaths annually worldwide. 3 MRI is a core component of cancer management in high-income countries as it enables early and accurate diagnosis of cancer, thereby facilitating the treatment of neoplasms at a stage when they are more likely to be treatable.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebrovascular implications of systemic disorders such as sickle cell disease with a high prevalence rate in SSA make neuroimaging particularly important in the region 20 . Beyond NCDs, MRI can play a paramount role in the management of infectious diseases, such as HIV and malaria 21–23 …”
Section: Introductionmentioning
confidence: 99%